Effects of barefoot and barefoot inspired footwear on knee and ankle loading during running - Sinclair, J. (Clinical Biomechanics, 2014)
Recreational runners frequently suffer from chronic pathologies. The knee and ankle have been highlighted as common injury sites. Barefoot and barefoot inspired footwear have been cited as treatment modalities for running injuries as opposed to more conventional running shoes. This investigation examined knee and ankle loading in barefoot and barefoot inspired footwear in relation to conventional running shoes.